Le street art à Naples - Christine Salomone (EchoGéo, 2018)
This article studies the role of street art in the urban transformation of a city in southern Italy, Naples, and its difficult valorisation. Fertile and emblematic soil of this urban art with early artistic experiences as early as the 1980s, Naples does not appear in the major street art destinations like Berlin, Barcelona or London. While other Italian cities such as Rome or Milan are thinking about new instruments and tools to promote street art tourism, the city is struggling to make this offer officially emerge. Yet spontaneous or non-spontaneous initiatives in favour of urban art from various neighbourhoods – at the margins of the historic centre or more peripheral neighbourhoods - have grown and become denser. Alongside artists, urban art promoters are plural (private, associative and institutional). They invest this field of culture with various objectives to make it a tool for urban renewal and creativity in deprived neighbourhoods. To envisage this articulation between the valorisation of street art and urban space, the article confronts private initiatives in two Neapolitan neighbourhoods, a margin of the historic centre, the Vergini-Sanità area and a more peripheral neighbourhood, Ponticelli. It questions the discourses and the play of the players and questions the nature of the valued spaces and the objectives sought.